Analisis Tingkat Kebisingan di Kawasan Kampus Universitas Putra Indonesia (UPI) di Kecamatan Lubuk Begalung Kota Padang - Fadjar Goembira; Taufiq Ihsan; Muhammad Fahyudi (Jurnal Dampak, 2016)
The purpose of this research is to analyze the data measuring the noise level in the campus of the University of Putra Indonesia (UPI). Measurement point exterior and interior consists of 12 points and 7 points. The measurement method is based on Decree of the Indonesia Minister of Environment No. 48 of 1996 on Baku Noise is a method simple way by using Sound Level Meter. The highest level of exterior noise when L1 at the point of the Campus Gate UPI (1A) of 73.72 dB (A). The noise level in the afternoon (LS) between 69.63 to 61.60 dB (A), the noise level night (LM) between 48.10 to 38.72 dB (A) and the day-night noise level (LSM) between 67.91 to 59.93 dB (A). The highest current interior noise levels of activity in Building D (2B) of 69.96 dB (A), while the highest level of interior noise occurs at the point when empty Building G (7B) of 69.37 dB (A). Value exterior noise when the time L1-L4 exceeds Raw Noise Level while the value of interior noise when the condition activity partly exceeded Raw Noise except Building G (7B) and the value of noise when empty condition partly exceeds the noise level except Building UPI Sport & Exhibition Hall (1B), Building B (3B) and Building A (4B). Control recommendations exterior form of vegetation while the interior of the control building construction improvements. Keywords: noise, University of Putra Indonesia (UPI) campus, exterior, interior, control alternative recommendationABSTRAKTujuan penelitian adalah menganalisis data pengukuran tingkat kebisingan di kawasan Kampus Universitas Putra Indonesia (UPI). Titik pengukuran eksterior dan interior terdiri atas 12 titik dan 7 titik. Metode pengukuran berdasarkan KepMen LH No. 48 Tahun 1996 tentang Baku Tingkat Kebisingan yaitu metode cara sederhana dengan menggunakan alat Sound Level Meter. Tingkat kebisingan tertinggi eksterior pada saat L1 di titik Pintu Gerbang Kampus UPI (1A) sebesar 73,72 dB(A). Tingkat kebisingan pada siang (LS) antara 69,63-61,60 dB(A), tingkat kebisingan malam (LM) antara 48,10-38,72 dB(A) dan tingkat kebisingan siang-malam (LSM) antara 67,91-59,93 dB(A). Tingkat kebisingan interior tertinggi saat aktivitas di Gedung D (2B) sebesar 69,96 dB(A) sedangkan tingkat kebisingan interior tertinggi saat kosong terjadi di titik Gedung G (7B) sebesar 69,37 dB(A). Nilai kebisingan eksterior saat waktu L1-L4 melebihi Baku Tingkat Kebisingan sedangkan nilai kebisingan interior saat kondisi aktivitas sebagian melebihi Baku Tingkat Kebisingan kecuali Gedung G (7B) dan nilai kebisingan saat kondisi kosong sebagian melebihi baku tingkat kebisingan kecuali Gedung UPI Sport & Exhibition Hall (1B), Gedung B (3B) dan Gedung A (4B). Rekomendasi pengendalian eksterior berupa penanaman vegetasi sedangkan pengendalian interior berupa perbaikan konstruksi bangunan.Kata kunci: kebisingan, kampus Universitas Putra Indonesia (UPI), eksterior, interior, rekomendasi alternatif pengendalian